The precariousness of knowledge workers (Part 2): forms and critiques of autonomy and self-representation. (1st April 2017) - ,; ,; ,
Abstract : This article introduces the second of a two-part Special Issue of this journal on the precariousness of knowledge workers. It aims to explore the ambivalences and liminal relations among autonomy, identification and task orientation, which – for knowledge workers – represent both a source of self-realisation and a generator of multiple and distinctive forms of precariousness. In particular, we focus on the forms and critiques of autonomy and self-representation that, in knowledge societies, extend far beyond the fact of being a self-employed worker. We argue that knowledge work is in fact sustained by devices of subjectivity which derive their power from being self-constructed and which provide tools for managing precarious lives.